US Investment Programmes to Sustain Technological Advantage over China (Economic and Political Thought, 2023)
The article’s primary goal is to present a thorough study of how the InflationReduction Act (IRA) has affected US economic competitiveness and theexecution of initiatives to reduce reliance on foreign markets for US business.This analysis evaluates these solutions in light of US technological advantagesand critically examines the main business assistance tools for manufacturingand energy technologies provided by the IRA Act.
Keywords: industrial policy, subsidies, tax credit, competitiveness